USE OF ASSESMENT TECHNOLOGY IN TEACHING THE TOPIC "CHROMIUM AND ITS COMPOUNDS" (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The application of Assesment technology in the study of the theme of "Chromium and its combination" can stimulate the growth of knowledge potential, independent thinking of students, thereby increasing the effectiveness of teaching.